Induced pluripotent stem cell derived macrophages as a cellular system to study salmonella and other pathogens. - Christine Hale; Amy Yeung; David Goulding; Derek Pickard; Kaur Alasoo; Fiona Powrie; Gordon Dougan; Subhankar Mukhopadhyay (PLoS ONE)
A number of pathogens, including several human-restricted organisms, persist and replicate within macrophages (Mφs) as a key step in pathogenesis. The mechanisms underpinning such host-restricted intracellular adaptations are poorly understood, in part, due to a lack of appropriate model systems. Here we explore the potential of human induced pluripotent stem cell derived macrophages (iPSDMs) to study such pathogen interactions. We show iPSDMs express a panel of established Mφ-specific markers, produce cytokines, and polarise into classical and alternative activation states in response to IFN-γ and IL-4 stimulation, respectively. iPSDMs also efficiently phagocytosed inactivated bacterial particles as well as live Salmonella Typhi and S. Typhimurium and were able to kill these pathogens. We conclude that iPSDMs can support productive Salmonella infection and propose this as a flexible system to study host/pathogen interactions. Furthermore, iPSDMs can provide a flexible and practical cellular platform for assessing host responses in multiple genetic backgrounds.